3(2x-2)=-2(4k-11)

Simple and best practice solution for 3(2x-2)=-2(4k-11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-2)=-2(4k-11) equation:


Simplifying
3(2x + -2) = -2(4k + -11)

Reorder the terms:
3(-2 + 2x) = -2(4k + -11)
(-2 * 3 + 2x * 3) = -2(4k + -11)
(-6 + 6x) = -2(4k + -11)

Reorder the terms:
-6 + 6x = -2(-11 + 4k)
-6 + 6x = (-11 * -2 + 4k * -2)
-6 + 6x = (22 + -8k)

Solving
-6 + 6x = 22 + -8k

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 6x = 22 + 6 + -8k

Combine like terms: -6 + 6 = 0
0 + 6x = 22 + 6 + -8k
6x = 22 + 6 + -8k

Combine like terms: 22 + 6 = 28
6x = 28 + -8k

Divide each side by '6'.
x = 4.666666667 + -1.333333333k

Simplifying
x = 4.666666667 + -1.333333333k

See similar equations:

| 21x-5=20x | | 1x+2y=-5 | | 2(y+9)=12-3(y+14)+3y | | 4x-23=3x+16 | | 6=2(1+w) | | 500=4x^2-40x+400 | | 2(x-12)=27 | | 9(m-3)=5m+9 | | 5(2a+7)=2(3a+4) | | 815/12=a | | 16+3x=19+21x | | -27.083x-16.819=-11.246 | | x+91=x+97 | | 11e=9e+4 | | 5+2x=9.50 | | 4d^2+64=0 | | 2x-3x=14 | | -3n+11-7n=-13 | | 2z-1=z+8-22 | | x+91=x+971 | | x^2-22xy-48y^2= | | x/4-10=-13 | | -3+11-7n=-13 | | 6c-12+4c=8c | | -3+9=a | | 81-(6*9)=1 | | 19f^2-17k-2=0 | | 3s-4+6s+7= | | 18x^2+9x-20=0 | | d^2-14d+13=0 | | -6/5=a | | 16x-5=105 |

Equations solver categories